2017
DOI: 10.14529/mmph170208
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Studies of Hydrogen Physisorption on Clear and Li-Doped Carbon Nanotubes

Abstract: The hydrogen adsorption on internal and external surfaces of clear and Lidoped carbon nanotubes of different radii are investigated to assess the effects of concavity and doping on hydrogen uptake and binding energy. We make density functional calculations with the exchange-correlation functionals PBE and CA. Modeling of H 2 adsorption on clear carbon tubes shows that only in case of internal sorption on narrow (5,5) nanotube energy of adsorption fall within the desirable range of 300-400 meV per H 2 molecule.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Previously, we showed that doping CNTs with Li atom increases the adsorption energy of H 2 molecule for single molecule adsorption, and the E bind of the hydrogen molecule adsorbed inside the nanotube is in the desirable range . However, the hydrogen uptake of a CNT@Li-based material could be accessed once we defined the maximum H 2 binding capability of the Li adatom.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously, we showed that doping CNTs with Li atom increases the adsorption energy of H 2 molecule for single molecule adsorption, and the E bind of the hydrogen molecule adsorbed inside the nanotube is in the desirable range . However, the hydrogen uptake of a CNT@Li-based material could be accessed once we defined the maximum H 2 binding capability of the Li adatom.…”
Section: Introductionmentioning
confidence: 98%
“…16−25 Previously, we showed that doping CNTs with Li atom increases the adsorption energy of H 2 molecule for single molecule adsorption, and the E bind of the hydrogen molecule adsorbed inside the nanotube is in the desirable range. 26 However, the hydrogen uptake of a CNT@Li-based material could be accessed once we defined the maximum H 2 binding capability of the Li adatom. To be more precise, we need to know the structural and energetic characteristics of CNT@Li +kH 2 complexes, k = 1, 2, ..., k max , where k max is the maximum quantity of H 2 molecules.…”
Section: Introductionmentioning
confidence: 99%